Cultural diversity is crucial for African neuroethics - Matshabane, OP; Mgweba-Bewana, L; Atuire, CA; de Vries, J; Koehly, LM (Springer Nature, 2022)
Mental health, neuroscience and neuroethics researchers must engage local African communities to enable discourses on cultural understandings of mental illness. To ensure that these engagements are both ethical and innovative, they must be facilitated with cultural competence and humility, because serious consideration of different contextual and local factors is critical.